# Find two numbers whose sum is 27 and product is 182.

Last updated date: 27th Mar 2023

•

Total views: 306.3k

•

Views today: 3.83k

Answer

Verified

306.3k+ views

Hint: Here first we assume two variables and write the equations according to the condition given in question and solve the equations to get one of the values of the variable and substitute in the equation to get another variable.

Complete step-by-step answer:

First let us assume the two numbers are x and y

Then according to question, we will be having two equations those are

\[x + y = {\text{2}}7\] …… (1)

\[xy = 182\] …… (2)

Equation 1 can be written as

$\Rightarrow$ \[x = {\text{2}}7 - y\] …… (3)

On putting the value of x in equation (3), we get

$\Rightarrow$ $\left( {27 - y} \right)\left( y \right) = 182$

Above equation can also be written as

$\Rightarrow$ ${y^2} - 27y + 182 = 0$

On splitting we get

$\Rightarrow$ ${y^2} - 13y - 14y + 182 = 0$

$\Rightarrow$ $\left( {y - 13} \right)\left( {y - 14} \right) = 0$

From the equation above either y = 13 or y = 14.

Putting the value of y in equation(1) we get \[x = 14\] when \[y = 13\] and \[x = 13\] when \[y = 14\]

Hence the two numbers are 13 and 14.

Note: In these types of questions first assume the variables and then write the equation according to the condition given in the question then solve the equations to get the value of the variables.Students should take care while assuming the variables and writing the equations according to the question.

Complete step-by-step answer:

First let us assume the two numbers are x and y

Then according to question, we will be having two equations those are

\[x + y = {\text{2}}7\] …… (1)

\[xy = 182\] …… (2)

Equation 1 can be written as

$\Rightarrow$ \[x = {\text{2}}7 - y\] …… (3)

On putting the value of x in equation (3), we get

$\Rightarrow$ $\left( {27 - y} \right)\left( y \right) = 182$

Above equation can also be written as

$\Rightarrow$ ${y^2} - 27y + 182 = 0$

On splitting we get

$\Rightarrow$ ${y^2} - 13y - 14y + 182 = 0$

$\Rightarrow$ $\left( {y - 13} \right)\left( {y - 14} \right) = 0$

From the equation above either y = 13 or y = 14.

Putting the value of y in equation(1) we get \[x = 14\] when \[y = 13\] and \[x = 13\] when \[y = 14\]

Hence the two numbers are 13 and 14.

Note: In these types of questions first assume the variables and then write the equation according to the condition given in the question then solve the equations to get the value of the variables.Students should take care while assuming the variables and writing the equations according to the question.

Recently Updated Pages

If a spring has a period T and is cut into the n equal class 11 physics CBSE

A planet moves around the sun in nearly circular orbit class 11 physics CBSE

In any triangle AB2 BC4 CA3 and D is the midpoint of class 11 maths JEE_Main

In a Delta ABC 2asin dfracAB+C2 is equal to IIT Screening class 11 maths JEE_Main

If in aDelta ABCangle A 45circ angle C 60circ then class 11 maths JEE_Main

If in a triangle rmABC side a sqrt 3 + 1rmcm and angle class 11 maths JEE_Main

Trending doubts

Difference Between Plant Cell and Animal Cell

Write an application to the principal requesting five class 10 english CBSE

Ray optics is valid when characteristic dimensions class 12 physics CBSE

Give 10 examples for herbs , shrubs , climbers , creepers

Write the 6 fundamental rights of India and explain in detail

Write a letter to the principal requesting him to grant class 10 english CBSE

List out three methods of soil conservation

Fill in the blanks A 1 lakh ten thousand B 1 million class 9 maths CBSE

Epipetalous and syngenesious stamens occur in aSolanaceae class 11 biology CBSE